A retrospective study of Pupingqinghua prescription versus Lianhuaqingwen in Chinese participants infected with SARS-CoV-2 Omicron variants - Dong, Yidan; Zhai, Wei; Fang, Bangjiang; Liu, Chenyang; Yuan, Suyun; Wang, Youhua; Song, Qixiang; Li, Hai; Chen, Bin; Cui, Dan; Wang, Jun; Wu, Qiong; et al. (Frontiers in Pharmacology, 2022)
Background: Coronavirus disease 2019 (COVID-19) seriously endangers global public health. Pupingqinghua prescription (PPQH) is an herbal formula from Traditional Chinese Medicine used for the treatment of SARS-CoV-2 infection. This paper aims to evaluate the clinical efficacy and safety of PPQH in Chinese participants infected with the SARS-CoV-2 omicron variant. Methods: A total of 873 SARS-CoV-2 (Omicron) infected patients were included. Among them, patients were divided into PPQH Group (653 cases) and LHQW group (220 cases) according to different medication. The effectiveness indicators（hematological indicators, Ct values of novel Coronavirus nucleic acid tests, viral load shedding time）and safety indicators (liver and kidney function, adverse events) were analyzed. Results: There was no significant difference in baseline characteristics between the PPQH group and the LHQW group except the gender; After the treatment, the levels of IL-5, IL-6, IL-10, NK cells, and INF-α of the patient in PPQH group showed a downward trend (p < 0.05); The viral load shedding time was 5.0 (5.0, 7.0) in PPQH group and 5.0 (4.0, 7.0) in LHQW group; Both PPQH and LHQW can shorten the duration of symptoms of fever, cough, sore throat; The re-positive rate of COVID-19 test were 1.5% in PPQH group and 2.3% in LHQW group. In terms of safety, the levels of γ-GTT decreased significantly (p < 0.01); Gastrointestinal reaction was the primary adverse reaction, and the reaction rate was 4.7% in PPQH group and 9.5% in LHQW group.; Conclusion: PPQH can shorten the length of hospital stay and improve clinical symptoms of patients with SARS-COV-2 (Omicron), and has a good safety profile.